On the Phosphite-Mediated Synthesis of Dithiafulvenes and π-Extended Tetrathiafulvalenes - Schou, Simon Stubbe; Parker, Christian Richard; Lincke, Kasper; Jennum, Karsten; Vibenholt, Johan; Kadziola, Anders; Nielsen, Mogens Brøndsted (Synlett, 2013)
By phosphite-mediated couplings between functionalized benzaldehydes and 1,3-dithiole-2-thiones we have obtained a variety of π-extended tetrathiafulvalenes (TTF). In particular, this method has provided a new stilbene-extended TTF with lateral alkyne functionalities, an H-type cruciform structure. This outcome is the result of a phosphite-mediated coupling between two aldehydes.
Keywords: cruciform; heterocycles; phosphite; sulfur; tetrathiafulvalene